1998
DOI: 10.1097/00005176-199803000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux and Nissen Fundoplication Following Percutaneous Endoscopic Gastrostomy in Children

Abstract: Percutaneous endoscopic gastrostomy is a safe and effective technique for long-term nutritional support in children. Abnormal gastroesophageal reflux is common. Normal findings in an esophageal pH study before percutaneous endoscopic gastrostomy may be predictive of a favorable outcome with respect to gastroesophageal reflux. This is in contrast to patients with abnormal results in pH studies before percutaneous endoscopic gastrostomy of whom a relatively large percentage may later require fundoplication. Impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
2
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 19 publications
1
56
2
2
Order By: Relevance
“…49 An earlier study by PayneJames looked at contaminated formula and retrograde movement of bacteria in tubing sets with no drip chamber, a drip chamber, and a drip chamber plus an anti-reflux valve. 46 Results showed no bacterial contamination of the EN formula when tubing with a drip chamber was used. 46 Two studies done in the Netherlands in intensive care unit (ICU) patients looked at bacterial contamination of enteral administration sets and found them to be unacceptably contaminated after a 24-hour hang time.…”
Section: 56mentioning
confidence: 89%
See 2 more Smart Citations
“…49 An earlier study by PayneJames looked at contaminated formula and retrograde movement of bacteria in tubing sets with no drip chamber, a drip chamber, and a drip chamber plus an anti-reflux valve. 46 Results showed no bacterial contamination of the EN formula when tubing with a drip chamber was used. 46 Two studies done in the Netherlands in intensive care unit (ICU) patients looked at bacterial contamination of enteral administration sets and found them to be unacceptably contaminated after a 24-hour hang time.…”
Section: 56mentioning
confidence: 89%
“…46 Results showed no bacterial contamination of the EN formula when tubing with a drip chamber was used. 46 Two studies done in the Netherlands in intensive care unit (ICU) patients looked at bacterial contamination of enteral administration sets and found them to be unacceptably contaminated after a 24-hour hang time. 48,60 These studies suggested that retrograde migration of bacteria from the stomach and lungs are a problem.…”
Section: 56mentioning
confidence: 89%
See 1 more Smart Citation
“…In children without s y m p t o m s o f r e f l u x o r w i t h m i l d r e f l u x responding well to medical treatment, an endoscopic percutaneous approach may be used. There is no role for a prophylactic antireflux procedure (Sulaeman et al, 1998, Isch et al, 1997. The choice between a gastrostomy with or without an anti-reflux procedure has to be carefully evaluated because the failure rate and the incidence of major complications are high in neurologically impaired children undergoing anti-reflux procedure (Borgstein et al, 1994).…”
Section: Gastroesophageal Reflux and Pulmonary Aspirationmentioning
confidence: 99%
“…The improvement of physical growth coupled with improvement in the general health and the family quality of life (Stevenson, 2005). Direct aspiration of orally ingested material and saliva may be a reason for recommending PEG tube feeding (Brant et al, 1999, Sulaeman et al, 1998. But gastroesophageal reflux is also thought to contribute to aspiration indirectly (Morton et al, 1999).…”
mentioning
confidence: 99%